Evaluation of rapid antigen detection test for group A Streptococci pharyngitis among children in an out-patient clinic in Malaysia - Zaili Zaki; Asrul Abdul Wahab; Ramliza Ramli; Afaaf Esa; Ezura Madiana Md. Monoto (Penerbit Universiti Kebangsaan Malaysia, 2021)
One of the most common conditions encountered in the out-patient setting is acute pharyngitis. Group A Streptococcus (GAS) accounts for 15%-30% of cases of sore throat particularly in children under 15 years old. Rapid antigen testing (RADT) is an alternative diagnostic method to detect GAS pharyngitis. This study was done to evaluate the agreement between RADT whereby BIONEXIA® Strep A Plus (BioMérieux, France) kit was used and throat culture in the diagnosis of GAS pharyngitis in children presented with a sore throat. One hundred and ten children from a primary health care clinic with sore throat were included in this study. All children were evaluated based on McIsaac scoring and throat swab samples were taken for both throat culture and RADT testing. The prevalence of GAS pharyngitis by RADT in this study was 7.3% over one year. A higher incidence of GAS pharyngitis was noted in the school-aged children than the preschool-age children. There was no correlation between cough, lymph node enlargement, and tonsillar enlargement in predicting GAS pharyngitis. The sensitivity and specificity of RADT were 100% and 98%, respectively, when taking throat culture as a gold standard. A good agreement between RADT and throat culture was achieved (k=0.848). McIsaac scoring was noted to have good predictability for GAS pharyngitis with AUC=0.82. In conclusion, the rapid streptococcal antigen detection test showed excellent sensitivity and specificity and detecting GAS from the throat swab samples. Thus, it can be used to aid in the diagnosis of group A Streptococcal pharyngitis and could reduce the overuse of antibiotics. McIsaac score has also proven to be useful as a screening tool for bacterial pharyngitis.